Knowledge of Occupational Diseases and Practice of Preventive Measures among Roadside Workers in Uyo Metropolis, Akwa Ibom State – Nigeria - R. D, Ebong; Eka , Aniefiok Ukpe (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The study was conducted to determine the level of knowledge of occupational diseases and practice of preventive measures among roadside workers in Uyo Metropolis, Akwa Ibom State. The purpose of the study was to determine the level of knowledge of occupational diseases and the practice of preventive measures among roadside workers in Uyo Metropolis. Two research questions were formulated for the study while one research hypothesis was tested. A cross-sectional survey design was adopted using a purposive sampling technique where 200 respondents were drawn for the study from four major roads in Akwa Ibom State. A fifteenth item questionnaire (KODPPMRW) was the only instrument used for data collection. Frequency and percentage was used to answer the research questions while Chi Square was used to test the hypothesis at .05 level of significance. The result of the study revealed that roadside workers have high knowledge about the diseases associated with their work which significantly influences the practice of preventive measures. Recommendation was on health education of roadside workers in Akwa Ibom State to stimulate their interest on the need for regular practice of preventive measures while at work